Les retours de Gulliver - Jean VIVIÈS (E-REA)
The essay focusses on Lemuel Gulliver’s returns to England in Jonathan Swift’s Gulliver’s Travels (1726). The traveller’s four returns at the end of each part emerge as crucial loci of the narrative which offer the reader insights into Gulliver‘s gradual disintegration. The gradual difficulty of the sailor’s successive returns culminates in the last return whose problematical meaning leads the reader to reconsider the overall interpretation of the text.